CANNING OF SMOKED SARDINE. - NAIR, T. S UNNIKRISHNAN; BALACHANDRAN, K K; MADHAVAN, P (Fishery Technology, 2017)
A process for canning smoked oil sardine (Sardinellalongiceps) is described. Cold blanching of dressed fish in brine,smoking followed by drying in hot air or cooking in steamto reduce the moisture content to the required level andsubsequent canning yields product with good organolepticproperties. Coconut husk is used as source of smoke.